PEDAGOGICAL SUPPORT FOR THE DEVELOPMENT OF INTERNATIONAL ACADEMIC MOBILITY IN THE POST-SOVIET SPACE - O. Aldakimova (Вестник Северо-Кавказского федерального университета, 2022)
The development of international academic mobility is considered in the article as a modern trend in scientific and technical cooperation between countries. Russian universities actively participate in the competition in the international market of educational services, which contributes to strengthening the authority of Russian education in the world. The high prestige of Russian education arouses increased interest among young people in the post-Soviet space. To more actively attract foreign students to Russian universities, Russian universities will have to create favorable learning conditions for them. The article presents the substantiation of the structure of pedagogical support for the development of international academic mobility in the post-Soviet educational space.